2007
DOI: 10.2119/2006-00107.trevino
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarrays: a Powerful Genomic Tool for Biomedical and Clinical Research

Abstract: Among the many benefits of the Human Genome Project are new and powerful tools such as the genome-wide hybridization devices referred to as microarrays. Initially designed to measure gene transcriptional levels, microarray technologies are now used for comparing other genome features among individuals and their tissues and cells. Results provide valuable information on disease subcategories, disease prognosis, and treatment outcome. Likewise, they reveal differences in genetic makeup, regulatory mechanisms, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(116 citation statements)
references
References 61 publications
0
114
0
2
Order By: Relevance
“…Using microarray technology (Trevino et al, 2007), we found here that the expression of 1 synaptic protein in particular, cerebellin 4 (Cbln4), increased on Hes1 overexpression. The cerebellins, cerebellin 1e4, make up a small family of secreted glycoproteins that belong to the C1q/tumor necrosis factor superfamily, and they are proteins that are essential for the specification, formation, and maintenance of the synapse (Eiberger and Schilling, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…Using microarray technology (Trevino et al, 2007), we found here that the expression of 1 synaptic protein in particular, cerebellin 4 (Cbln4), increased on Hes1 overexpression. The cerebellins, cerebellin 1e4, make up a small family of secreted glycoproteins that belong to the C1q/tumor necrosis factor superfamily, and they are proteins that are essential for the specification, formation, and maintenance of the synapse (Eiberger and Schilling, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…The human genome comprehends 3.2 billion bases and 30,000–40,000 protein-coding genes. DNA microarrays provide a measurement of DNA sequence differences among individuals, and the expression of thousands of genes can be analyzed simultaneously [22, 23]. Transcriptomics examines genome RNA levels, both qualitatively (transcripts types, new splice sites, RNA editing sites) and quantitatively (the expressed quantity of each transcript).…”
Section: Genomics and Transcriptomicsmentioning
confidence: 99%
“…Of note, the list of the mechanisms of action classically ascribed to ω-3 PUFAs has further grown in recent years by the applications of high-throughput genomic tools that allow the simultaneous comparison of thousands of genes and gene-products in a fashion not biased or restricted by a priori hypotheses [49]. Besides confirming the down-regulation of proinflammatory genes by ω-3 PUFAs [50], this approach has disclosed positive modulatory activities for previously unsuspected genes and gene products involved in the regulation of lipid metabolism and antioxidant enzyme systems [51][52][53].…”
Section: Plant-and Marine-derived ω-3 Pufas: Mechanisms Of Actionmentioning
confidence: 99%